1) The velocity of the particle is given by the derivative of the position. So, if we derive s(t), we get the velocity of the particle as a function of the time:
![v(t)=s'(t)=(2t^3-3t^2-36t+6)'=6t^2-6t-36](https://img.qammunity.org/2019/formulas/physics/college/ycctfpemr247gsnzalu73v5pvf0g7sdiuf.png)
2) The acceleration of the particle is given by the derivative of the velocity. So, if we derive v(t), we get the acceleration of the particle as a function of the time:
![a(t)=v'(t)=(6t^2-6t-36)'=12t-6](https://img.qammunity.org/2019/formulas/physics/college/6wjm3ram9mi2yh1wrecz4qxyvqf5kuk68g.png)